Fontes e manejo de nitrogênio na cultura da batata em solos arenosos - Souza, Emerson de Freitas Cordova de [UNESP] (2014)
Potato plant (Solanum tuberosum L.) is one of the most grown species in the world. Nitrogen deficiency is one of the factors that limit this crop, because it is directly linked to the tuber yield. Thus, a study seeking the best strategy for the potato nitrogen utilization becomes necessary, mostly when it is grown in sandy soils. The objective of this work was to evaluate the behavior and chemical changes of soil after application of urea, ammonium sulfate and ammonium sulfonitrate, containing the nitrification inhibitor-DMPP, known commercially as Entec® 26; the effect of these sources and the nitrogen application rates on potato cropped in sandy soil, and more specifically, the effect of rates and split application of Entec on potato cropped in sandy soil. This way, a laboratory experiment in a completely randomized design, with four replications under constant temperature and humidity, and six experimental field, with four blocks in a randomized block design were carried out. The laboratory experiment had three fertilized treatments, (addition of Entec, ammonium sulfate, and urea) and one unfertilized as a control. For experiments I, II and III, a factorial design 3 x 3 + 1 was used. The treatments comprised three types of nitrogenous fertilizers applied (Entec, ammonium sulfate, and urea), as well as three rates of N (80, 120, and 160 kg ha-1) and one without nitrogen application as a control. On experiments IV, V, VI, the treatments comprised two rates (120 and 160 kg ha-1) of Entec fertilizer. It was either totally applied at planting or it was split applied (40 kg ha-1 at planting; remainder split applied). There was one unfertilized as a control. Urea increased the pH quickly and strongly, however, later on the pH decreased and promoted the greatest soil acidification. Besides, it was more nitrified than ammonium sulfate and Entec fertilizers. Entec kept the initial NO3- availability stable ...